A study of diesel particulate filter impact on engine oil quality - Hurtová, Ivana; Sejkorová, Marie; Verner, Jan (Kaunas University of Technology, 2019)
The paper presents the results of analyzes based on which the setting of change intervals of Castrol SLX, SAE 0W-30 synthetic engine oil used in D5 diesel engines of Volvo cars was verified. ACEA oils of A5/B5 specification recommended for engines complying with EURO 4 emission standards, ie oils from vehicles with DPF, were analyzed. Also, ACEA engine oils of A3/B3 specification, which were taken from cars complying with EURO 3 emission standards (ie without DPF) during service inspections, were analyzed. Based on the results of evaluation of a large scale of oil samples, it has been proved that the engine oil was contaminated with diesel during the DPF filter regeneration process. In some cases, contamination by fuel was so high that the oil viscosity was reduced to half its original value. Therefore, it was recommended to shorten the oil change interval. No significant degradation or contamination was detected in the monitoring of the condition of oils taken from EURO 3 engines.
Studium vlivu filtru pevných částic na kvalitu motorového oleje
Keywords: change interval; engine oil; lubricant; diesel particulate filter (DPF); dilution with diesel; common-rail systems; výměnný interval; motorový olej; mazivo; filtr pevných částic; průnik paliva